Asterix and the Cauldron - Goscinny, Rene (Orion Publishing Group Ltd, 2004)
Financial skulduggery in ancient Gaul! When local chief Whosemoralsarelastix wants a cauldron full of money kept out of Roman hands, the cash disappears while Asterix is guarding it...
Keywords: Graphics